Yurisdiksi Mahkamah Pidana Internasional Terhadap Penegakan Hukum Bagi Pelaku Kejahatan Perang Yang Bukan Negara Pihak Statuta Roma 1998 - Patty, Jetty Martje; Makaruku, Steven (Fakultas Hukum Universitas Pattimura, 2024)
Introduction: The establishment of a permanent International Criminal Court (ICC) has opened a new history in law enforcement crimes of genocide, humanity, war, aggression. The Roma Statute of 1998 became the constitutional basis for International Criminal Court.Purposes of the Research: To find out the jurisdiction of the International Criminal Court to enforce the law for perpetrators of war crimes war that is not a state party to the Roma Statute of 1998.Methods of the Research: The method used in this study is normative juridical with an approach to international legal regulations and concepts. The sources of legal materials used in this study are primary legal materials, secondary legal materials and tertiary legal materials.Results of the Research: The results of the discussion are that in the ICC efforts to enforce the law based on the provisions of article 12 concerning the requirements for exercising jurisdiction related to the ICC issuing an arrest warrant for Vladimir Putin is contrary to the provisions of article 12 paragraph (1) which confirms that the country that is a party to this statute, thus accepting the jurisdiction of the court with regard to the crimes referred to in article 5. This is because both Rusia and Ukraina are countries that are not parties to the Roma Statute 1998, so that the arrest warrant against Vladimir Putin is null and void. However , there is an exception in article 13 paragraph (3) of the statute which state that if a state which is not a state party declares that it accepts this statute and ratifies this statute, then the ICC can exercise its jurisdiction over the state which has accepted the jurisdiction of the ICC. So that the attempt to arrest Vladimir Putin can be carried out constitutionally under the statute.